2017
DOI: 10.1016/j.worlddev.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Does Large-Scale Infrastructure Investment Alleviate Poverty? Impacts of Rwanda’s Electricity Access Roll-Out Program

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(162 citation statements)
references
References 24 publications
8
126
0
2
Order By: Relevance
“…Access to modern and sustainable energy and increased energy efficiency are fundamental for eliminating poverty [43]. Some studies have examined the causal relationship between electrification and human wellbeing [47][48][49][50] revealing evidence of the positive relationship between access to electricity (T7.1) and household income (T1.1 and T1.3) in Bangladesh, Nepal, Brazilian Amazon and Rwanda, respectively. Improved efficiency in the use of biomass (T7.3) in developing countries could help to meet a growing energy demand with renewable sources, reducing energy poverty (T1.1 and T1.2) [51].…”
Section: Sdg1 In Focus-poverty Eradicationmentioning
confidence: 99%
“…Access to modern and sustainable energy and increased energy efficiency are fundamental for eliminating poverty [43]. Some studies have examined the causal relationship between electrification and human wellbeing [47][48][49][50] revealing evidence of the positive relationship between access to electricity (T7.1) and household income (T1.1 and T1.3) in Bangladesh, Nepal, Brazilian Amazon and Rwanda, respectively. Improved efficiency in the use of biomass (T7.3) in developing countries could help to meet a growing energy demand with renewable sources, reducing energy poverty (T1.1 and T1.2) [51].…”
Section: Sdg1 In Focus-poverty Eradicationmentioning
confidence: 99%
“…Interestingly, a handful of the studies also examining the impact of electrification on respiratory health conditions found no evidence of a positive effect. Lenz, Munyehirwe, Peters, and Sievert (2017), for instance, investigated the effects of the Electricity Access Role-Out Program (EARP) in Rwanda using a mixed-methods study design, which combined a non-randomised controlled trial, a descriptive cross-sectional survey of health centres, and qualitative surveys at the household, micro-enterprise, community chief, health centre, and school levels (Lenz et al, 2017). The authors found that approximately 40% of households in areas serviced by EARP reported an improvement in air quality within the home, due specifically to reduced kerosene usage following electrification, however no change in self-reported respiratory disease, eye disease, or headaches was observed (Lenz et al, 2017).…”
Section: Health Effects Of Electrificationmentioning
confidence: 99%
“…Lenz, Munyehirwe, Peters, and Sievert (2017), for instance, investigated the effects of the Electricity Access Role-Out Program (EARP) in Rwanda using a mixed-methods study design, which combined a non-randomised controlled trial, a descriptive cross-sectional survey of health centres, and qualitative surveys at the household, micro-enterprise, community chief, health centre, and school levels (Lenz et al, 2017). The authors found that approximately 40% of households in areas serviced by EARP reported an improvement in air quality within the home, due specifically to reduced kerosene usage following electrification, however no change in self-reported respiratory disease, eye disease, or headaches was observed (Lenz et al, 2017). Bridge, Adhikari, and Fontenla (2016) similarly observed a positive but non-significant association between household electricity connections and respiratory health expenditures among rural households in Nepal, using a cross-sectional study design (Bridge et al, 2016).…”
Section: Health Effects Of Electrificationmentioning
confidence: 99%
“…The impact of electricity access for development is confirmed by several scientific and applied case studies which revealed significant positive impacts, for example on household income, expenditure, health care, and educational outcomes [15][16][17][18][19][20][21][22][23][24][25]. In particular for grid [26], SHS [27] and mini-grid [28] electrification the beneficial impacts on households with regard to illumination and access to information have been underlined while a direct economic impact remains uncertain for grid [26] and SHS [27] based approaches.…”
Section: Literature Reviewmentioning
confidence: 94%